If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 12 = 2(4z + -7) Reorder the terms: 12 + z = 2(4z + -7) Reorder the terms: 12 + z = 2(-7 + 4z) 12 + z = (-7 * 2 + 4z * 2) 12 + z = (-14 + 8z) Solving 12 + z = -14 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. 12 + z + -8z = -14 + 8z + -8z Combine like terms: z + -8z = -7z 12 + -7z = -14 + 8z + -8z Combine like terms: 8z + -8z = 0 12 + -7z = -14 + 0 12 + -7z = -14 Add '-12' to each side of the equation. 12 + -12 + -7z = -14 + -12 Combine like terms: 12 + -12 = 0 0 + -7z = -14 + -12 -7z = -14 + -12 Combine like terms: -14 + -12 = -26 -7z = -26 Divide each side by '-7'. z = 3.714285714 Simplifying z = 3.714285714
| 6+4(3-4x)=-2(1+3x) | | 15/3=x/5 | | 2(-2x-5)+4x=10 | | -5(5y-5)+2(2y+5)= | | (2x+5y)+(x+y)=1 | | z+12=4z-7 | | 90+90+(2x-4)+(3x-29)=360 | | 45x-9y=18 | | -9=3x+5 | | 4x^2+45=20x | | 848/0 | | w(w-6)=0 | | 8t+2(1-5t)= | | 4x^2+28x=-61 | | -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 | | 2/5=x/25 | | 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) | | -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x |